Legal Uncertainty and Structural Injustice of Platform Workers: Reasserting the State’s Responsibility in Legal Protection - Trianah Sofiani; Suci Flambonita; Yunas Derta Luluardi; Ridoan Karim (Jurnal IUS Kajian Hukum dan Keadilan, 2026)
The development of the platform economy in Indonesia has significantly transformed employment patterns, yet this transformation has not been companied by an adequate legal framework, resulting in legal uncertainty and structural injustice. This study aims to examine the structural roots of such uncertainty, analyse the problems in the relationship between platform companies and workers, and reaffirm the state’s responsibility to ensure legal certainty. Adopting an empirical juridical method with doctrinal and non-doctrinal approaches, the study finds that legal uncertainty is driven by multidimensional factors. These include the failure to internalise justice principles in the protection of platform workers, regulatory framework that remain ad hoc, sectoral, and frequently changing, a political configuration influenced by market logic and capitalism, and a gap between the evolving practices of platform work and the existing legal framework. These conditions create ambiguity in worker status and reinforce structural injustice in employment relations. In this context, the state is required to perform a corrective function to address structural inequality by recognising worker status, providing protection that ensures legal certainty and effectiveness, and regulating the distribution of economic risks and benefits in a fair and proportional manner. This study proposes a conceptual framework based on three pillars—recognition, protection, and redistribution—as a foundation for adaptive and progressive legal reform, while also contributing theoretically and practically to the development of labour law in the digital era.